Characterization and Molecular Subtyping of Shiga Toxin–Producing Escherichia coli Strains in Butcher Shops - Brusa, Victoria (2017)
AbstractShiga toxin–producing Escherichia coli (STEC) are important emerging foodborne human pathogens. Ruminants are the main animal reservoir of STEC currently known, and meat can become contaminated at different stages of the production chain. The aim of this work was to subtype and establish the epidemiological relatedness of non-O157 STEC strains isolated from ground beef and the environment in butcher shops before (evaluation stage, 2010–2011 period) and after (verification stage, 2013) implementing improvement actions. Sixty-eight non-O157 STEC strains were tested for eae, saa, ehxA, iha, efa1, toxB, subAB, cdt-V, astA, aggR, and aaiC genes, and stx1 and stx2 variants were determined. Pulsed-field gel electrophoresis (PFGE) was carried out with XbaI and XmaJI. From the 68 strains, 92.6%, 75.0%, 58.8%, 53.5%, 10.3%, 7.3%, and 4.4% were positive for iha, ehxA, subAB, saa, cdt-V, astA, and eae, respectively. All strains were aggR/aaiC-negative. PFGE showed that 19 strains grouped in 9 clusters and 41 showed unique XbaI patterns. During the evaluation stage (2010–2011), we identified clonal strains in different samples, circulating clones in different butcher shops, and more than one different strain in the same butcher shop. The bovine origin of meat and its manufacturing process could not ensure the total absence of all non-O157 STEC serotypes in this foodstuff. Most strains isolated during the evaluation (2010–2011) and verification (2013) stages did not exhibit a genotypic profile associated with human disease. It is necessary to conduct periodic reviews of the new epidemiological information and verify that the analyses of non-O157 STEC in food are appropriate to identify strains affecting the population.